2016
DOI: 10.1016/j.nimb.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Charged defects during alpha-irradiation of actinide oxides as revealed by Raman and luminescence spectroscopy

Abstract: We have recently evidenced an original Raman signature of alpha irradiation-induced defects in UO 2. In this study, we aim to determine whether the same signature also exists in different actinide oxides, namely ThO 2 and PuO 2. Sintered UO 2 and ThO 2 were initially irradiated with 21 MeV He 2+ ions using a cyclotron device and were subjected to an in situ luminescence experiment followed by Raman analysis. In addition, a PuO 2 sample that has previously accumulated self-irradiation damage due to alpha partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
4
21
1
Order By: Relevance
“…The intensity of the defect peaks increases as a function of electron energy and is consistent with the increase defects concentration in the UO 2 samples. However, the intensity increase observed in this study is less prominent compared to data reported for alpha and heavy-ion irradiation [10,11,25]. Though the Raman defect bands appear clearly for the 2.5 MeV irradiated disk, it is difficult to estimate the electron energy threshold for the defect peaks from Figure 1.…”
Section: Raman Spectra Analysiscontrasting
confidence: 90%
See 2 more Smart Citations
“…The intensity of the defect peaks increases as a function of electron energy and is consistent with the increase defects concentration in the UO 2 samples. However, the intensity increase observed in this study is less prominent compared to data reported for alpha and heavy-ion irradiation [10,11,25]. Though the Raman defect bands appear clearly for the 2.5 MeV irradiated disk, it is difficult to estimate the electron energy threshold for the defect peaks from Figure 1.…”
Section: Raman Spectra Analysiscontrasting
confidence: 90%
“…Figure 1 shows that electron irradiation induces the apparition of the Raman triplet defect bands in the 500-700 cm -1 spectral range, denoted by U1 (~532 cm -1 ), U2 (~574 cm -1 ) and U3 (~636 cm -1 ). First of all, these spectra look rather similar to those previously obtained under ionic irradiation [10,11]. The T 2g mode looks only slightly affected and the three defect lines occur.…”
Section: Raman Spectra Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…We must note that our Raman measurements have been performed with a 532 nm wavelength laser. In these analysis conditions, the LO band is much more intense compared to the U1 and U3 bands due to a resonance effect [16].…”
Section: Resultsmentioning
confidence: 98%
“…Estimated O/M ratio T (K) y = 0.018 y = 0.077 y = 0.21 y = 0.49 y = 0.80 y = 1.00 disorder induced by the recoil nuclei of the decays (Chikalla & Turcotte, 1973;Noe & Fuger, 1974;Hurtgen & Fuger, 1977;Weber, 1984;Sykora et al, 2005;Baclet et al, 2007;McCall et al, 2008;Kato et al, 2009;Belin et al, 2009;Prieur et al, 2011Prieur et al, , 2014Horlait et al, 2013;Lebreton et al, 2014;Strach et al, 2014;Mohun et al, 2016). Since the present samples were annealed in situ prior to the measurements and because the analysis duration was relatively short (about 1 d), the swelling effect induced by selfirradiation on the lattice was not observed.…”
Section: Lattice Parameters At Room Temperaturementioning
confidence: 99%